Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin